Advanced style - Cohen, Ari Seth.; Kalman, Maira; Von Teese, Dita, 1972- (Brooklyn, N.Y. : Power House Books, 2012)
Advanced Style is Ari Seth Cohen's blog-based ode to the confidence, beauty, and fashion that can only be achieved through the experience of a life lived glamorously. It is a collection of street fashion unlike any seen before - focused on the over-60 set in the world's most stylish locales. The (mostly) ladies of Advanced Style are enjoying their later years with grace and panache, marching to the beat of their own drummer. These timeless images and words of wisdom provide fashion inspiration for all ages and prove that age is nothing but a state of mind--
boek
Keywords: Cohen, Ari Seth